-7q-13=4q-7q

Simple and best practice solution for -7q-13=4q-7q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7q-13=4q-7q equation:


Simplifying
-7q + -13 = 4q + -7q

Reorder the terms:
-13 + -7q = 4q + -7q

Combine like terms: 4q + -7q = -3q
-13 + -7q = -3q

Solving
-13 + -7q = -3q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '3q' to each side of the equation.
-13 + -7q + 3q = -3q + 3q

Combine like terms: -7q + 3q = -4q
-13 + -4q = -3q + 3q

Combine like terms: -3q + 3q = 0
-13 + -4q = 0

Add '13' to each side of the equation.
-13 + 13 + -4q = 0 + 13

Combine like terms: -13 + 13 = 0
0 + -4q = 0 + 13
-4q = 0 + 13

Combine like terms: 0 + 13 = 13
-4q = 13

Divide each side by '-4'.
q = -3.25

Simplifying
q = -3.25

See similar equations:

| 3v^2-7v-20=0 | | (2z-1)(4z-4)=0 | | x^3-2x^2-35x+78=0 | | logn=2 | | 7u-56=3u+12 | | 4x-10+2x=4-(6x-9) | | 8*n^2=64*n*log(n) | | 8*n^2=64*n*log(2)n | | s^2-2s+4=0 | | 12x-5=40x+16 | | 8n^2=64nlog(n) | | x+d=ax | | (-3-2i)-(2-2i)= | | x=6*-15 | | y=0.6x+20 | | 3(x-5)-13=x+1 | | 2x+y=900 | | 100=0.6x+20 | | 5+3x-37=6x+23-8x | | 11(k-1)=7(k+9) | | 3+77x=44x+12 | | -6x-3+3x=6x+3 | | 12x-3y=18 | | 9m-3(m+6)=2(m+1)Simple | | 7u-u=24 | | 2x^3+12x^2=0 | | z^2-20z=-17 | | 77=6s+7x-82 | | 4x-3y+8=0 | | 36=(x-2)*(x+7) | | .8n=50337 | | z^2-10z=-17 |

Equations solver categories